2015
DOI: 10.1161/jaha.114.001588
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Reduction in Inflammation and Changes in Lipoprotein Levels and HDL Cholesterol Efflux Capacity in Rheumatoid Arthritis

Abstract: BackgroundPotent anti‐inflammatory rheumatoid arthritis (RA) treatments are associated with reduced cardiovascular risk as well as increases in low‐density lipoprotein (LDL) cholesterol. This apparent paradox may be explained by favorable changes in other lipid measurements. The objective of this study was to determine the longitudinal association between changes in inflammation with advanced lipoprotein measurements and high‐density lipoprotein (HDL) cholesterol efflux capacity.Methods and ResultsWe conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 50 publications
(95 reference statements)
6
87
1
5
Order By: Relevance
“…In this context, the finding of a significant association between apo A-I levels and cf-PWV can be a consequence of increased vascular damage in RA patients with decreased apo A-I concentration. In fact, a recent study showed that antiinflammatory treatment was associated with an increase in HDL cholesterol efflux capacity and apo A-I levels in RA patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the finding of a significant association between apo A-I levels and cf-PWV can be a consequence of increased vascular damage in RA patients with decreased apo A-I concentration. In fact, a recent study showed that antiinflammatory treatment was associated with an increase in HDL cholesterol efflux capacity and apo A-I levels in RA patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…In an observational study of rheumatoid arthritis patients with visits one year apart, reductions in high sensitivity (hs)CRP of more than 10 mg/dL were strongly associated with increases in LDL, apolipoprotein A1, HDL, and HDL cholesterol efflux capacity 71. No associations were seen with changes in hsCRP and apolipoprotein B or atherogenic indices (total cholesterol/HDL and apoliporotein B/A1).…”
Section: Mechanisms Linking Rheumatoid Arthritis and Cardiovascular Dmentioning
confidence: 98%
“…As expected, elevated levels of LDL-C are associated with increased CV risk in RA; however, low LDL-C is also associated with increased CV risk 2. Subjects with RA who experience a reduction in inflammation, considered beneficial for CV risk, have concomitant increases in LDL-C,3 suggesting the opposite effect of increased CV risk. Post hoc studies of lipids from randomised controlled trials of RA therapies have shown that increases in LDL-C occur across different classes of RA therapies 4.…”
mentioning
confidence: 74%
“…While the expected relationship of higher HDL-C levels and reduced CV risk is preserved in RA, cholesterol efflux capacity is impaired in RA subjects. Furthermore, a reduction in inflammation is associated with significant improvements in cholesterol efflux capacity,3 suggesting that HDL dysfunction may explain some of the excess CV risk in RA. Studying HDL function is a focus of the study presented by O'Neill et al 6 in this journal .…”
mentioning
confidence: 99%